Diarrheal disease control and family planning: the status of women and community participation - Wagner, Marsden G. (The Turkish Journal of Pediatrics, 1986)
In a lecture presented during the XXXth Congress of the Turkish National Pediatric Society in March 1986 in Ankara, the author points out how the social and educational status of women in Turkey and their participation in the community have an effect on the control of diarrheal diseases and the practice of family planning.